Efficacy and safety of hypoglycemic drugs in improving cognitive function in patients with Alzheimer's disease and mild cognitive impairment: A systematic review and network meta-analysis - Wang, Xin-Chen; Chu, Chen-Liang; Li, Han-Cheng; Lu, Kuan; Liu, Cheng-Jiang; Cai, Ye-Feng; Quan, Shi-Jian; Zhang, Shi-Jie (Frontiers in Neurology, 2022)
Objective The purpose of this study was to compare the effects of oral hypoglycaemic drugs (HDs) on cognitive function and biomarkers of mild cognitive impairment (MCI) and Alzheimer's disease (AD) through a network meta-analysis of randomized controlled trials (RCTs). Methods We conducted systematic searches for English- and Chinese-language articles in the PubMed, Medline, Embase, Cochrane Library and Google Scholar databases, with no date restrictions. We performed a network meta-analysis, which we report here according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The 16 studies included a total of 3,081 patients. We selected the Mini-Mental State Examination (MMSE), the Alzheimer's Disease Assessment Scale-Cognitive section (ADAS-Cog), the Alzheimer's Disease Cooperative Study Activities of Daily Living section (ADCS-ADL) and amyloid beta (Aβ) 42 as the outcome measures for analysis and comparison. Result We selected seven treatments and assessed the clinical trials in which they were tested against a placebo control. Of these treatments, intranasal insulin 20 IU (ITSN20), glucagon-like peptide-1 (GLP-1), and dipeptidyl peptidase 4 inhibitor (DPP-4) were associated with significantly improved MMSE scores (7 RCTs, 333 patients, 30≥MMSE score≥20: mild) compared with placebo [standardized mean difference (SMD) 1.11, 95% confidence interval (CI) (0.87, 1.35); SMD 0.75, 95% CI (0.04, 1.41); and SMD 4.08, 95% CI (3.39, 4.77), respectively]. Rosiglitazone 4 mg (RLZ4), rosiglitazone 10 mg (RLZ10), intranasal insulin 40 IU (ITSN40), and ITSN20 significantly decreased ADAS-Cog scores (11 RCTs, 4044 patients, 10 ≤ ADAS-Cog scores ≤ 30: mild and moderate) compared with placebo [SMD −1.40, 95% CI (−2.57, −0.23), SMD −3.02, 95% CI (−4.17, −1.86), SMD −0.92, 95% CI (−1.77, −0.08), SMD −1.88, 95% CI (−3.09, −0.66)]. Additionally, ITSN20 and ITSN40 significantly improved ADCS-ADL scores (2 RCTs, 208 patients, ADCS-ADL scale score ≤ 10: mild) compared with placebo [SMD 0.02, 95% CI (0.01, 0.03), and SMD 0.04, 95% CI (0.03, 0.05), respectively]. In the 16 included studies, the degree of AD was classified as mild or moderate. For mild cognitive impairment, DPP-4 performed best, but for mild to moderate impairment, ITSN40 had excellent performance. Conclusion Various HDs can improve the cognitive function of MCI and AD patients. Different drug regimens brought different degrees of improvement, which may be related to their dosage, duration, and mechanism of action. Systematic review registration www.crd.york.ac.uk/prospero.